Groundwater Nitrogen: Behavior in Flatwoods and Gravel Soils Using Organic Amendments for Vegetable Production - Sanjay Shukla; Edward A. Hanlon; Fouad H. Jaber; Peter J. Stoffella; Thomas A. Obreza; Monica Ozores-Hampton (EDIS)
Circular 1494, a 9-page illustrated circular by Sanjay Shukla, Edward A. Hanlon, Fouad H. Jaber, Peter J. Stoffella, Thomas A. Obreza, and Monica Ozores-Hampton, explores the use of several compost sources in vegetable production fields at Ft. Pierce and Homestead, Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, August 2006.